The Path to Impulse: A Cognitive-Affective-Conative Model of Live E-Commerce Behaviour Across Southeast Asia - Wusko, Any Urwatul; Aminullah, Aminullah (The South East Asian Journal of Management, 2026)
Research Aims: This study investigates how cognitive and affective mechanisms jointly shape impulse buying intentions in live e-commerce environments, using the Cognitive-Affective-Conative (CAC) model, with a focus on Southeast Asian consumers. Design/Methodology/Approach: A quantitative, cross-sectional survey was conducted with 430 respondents from Indonesia, Malaysia, Thailand, Vietnam, and the Philippines. Data were gathered from participants with recent live-shopping experience on platforms such as TikTok Shop and Shopee Live. Structural Equation Modelling (SEM) using SmartPLS was employed to test the proposed relationships. Research Findings: Perceived authenticity and interactivity significantly influence emotional arousal and fear of missing out, which in turn predicted impulse buying intention. Emotional arousal emerged as the strongest direct and mediating predictor. All ten hypotheses were supported. Theoretical Contribution/Originality: The study extends the CAC model to live e-commerce and demonstrates its robustness in collectivist, mobile-first Southeast Asian contexts. It distinguishes between arousal- and anxiety-based affective pathways, offering a refined perspective on digital impulse buying behaviour. Managerial Implications in the Southeast Asian Context: Strategies that enhance authenticity, facilitate real-time interaction, and tactically trigger emotional arousal and FOMO can significantly improve conversion rates in live commerce. Research Limitation & Implications: The cross-sectional design limits the ability to infer causality. Future research should incorporate experimental or longitudinal designs and explore differences among cultural subgroups.